2015
DOI: 10.17660/actahortic.2015.1086.17
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock-Mediated Variation in Tomato Vegetative Growth Under Drought, Salinity and Soil Impedance Stresses

Abstract: There is increasing interest in using novel rootstocks to confer resistance to abiotic stresses in horticultural species, and to understand the physiological mechanism(s) conferring these responses. The same scion (Solanum lycopersicum cv. Boludo F1, Monsanto) was grafted onto 144 different rootstocks: six accessions from S. lycopersicum (cv cerasiforme) and S. pimpinellifolium, selected for drought tolerance (sourced from AVRDC); nine introgression lines from S. lycopersicum x S. pennellii and x S. habrochait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Shoot biomass of the non-grafted scion was reduced by 30% under low-K compared to control conditions (Albacete et al, 2015a). The H rootstocks produced 40–50% more SFW than the L ones, while low-K decreased ( HcLk ) or increased ( LcHk ) shoot biomass by 25–30%, compared to control conditions (Figure 1A, Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Shoot biomass of the non-grafted scion was reduced by 30% under low-K compared to control conditions (Albacete et al, 2015a). The H rootstocks produced 40–50% more SFW than the L ones, while low-K decreased ( HcLk ) or increased ( LcHk ) shoot biomass by 25–30%, compared to control conditions (Figure 1A, Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The use of RILs has proven to be a useful tool for these and other purposes (Albacete et al, 2009, 2015a,b; Estañ et al, 2009; Asins et al, 2010). Using 114 RILs from a S. lycopersicum × S. pimpinellifolium cross as rootstocks of a commercial tomato cultivar generate a 2.5-fold variation in the vegetative growth of the scion growing under low-K supply (1 mM; Albacete et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, some accessions behaved as tolerant to both stresses, ranking theirself as the most interesting plant material for further research. Few studies can be found in which a rootstock can tolerate both water scarcity and salinity, and mainly are done in woody plants, such as grapevine (Walker et al 2002;Meggio et al 2014) and citrus (García-Sánchez et al, 2007;Rewald et al, 2012;Syvertsen et al, 1988), finding only some in tomato (Albacete et al, 2015). None of the studied 277 | C h a p t e r 8 accessions belong C. frutescens and C. pubescens shown tolerances to both water and salt stress screening experiments, being discarded in the next experiments.…”
Section: Discussionmentioning
confidence: 99%